A comparison of the effectiveness of an adult nutrition education program for Aboriginal and non-Aboriginal Australians. (November 2015) - Pettigrew, Simone; Jongenelis, Michelle I.; Moore, Sarah; Pratt, Iain S.
Abstract: Background: Adult nutrition education is an important component of broader societal efforts to address the high prevalence of nutrition-related diseases. In Australia, Aboriginal people are a critical target group for such programs because of their substantially higher rates of these diseases. Objective: The aim of this study was to assess the relative effectiveness of an adult nutrition education program for Aboriginal and non-Aboriginal participants. Methods: Pre-and post-course evaluation data were used to assess changes in confidence in ability to buy healthy foods on a budget, nutrition knowledge, and dietary behaviours among individuals attending FOODcents nutrition education courses. The total sample of 875 Western Australians included 169 who self-identified as Aboriginal or Torres Strait Islander. Results: Perceptions of course usefulness were very high and comparable between Aboriginal and non-Aboriginal participants. Significantly larger improvements in confidence, nutrition knowledge, and reported consumption behaviours were evident among Aboriginal participants. Conclusion: The findings suggest that adult nutrition education programs that address specific knowledge and skill deficits that are common among disadvantaged groups can be effective for multiple target groups, and may also assist in reducing nutrition-related inequalities. Highlights: Assesses knowledge and behaviour outcomes of a nutrition education program. Compares outcomes across Aboriginal and non-Aboriginal participants. Provides evidence of efficacy across both groups, especially Aboriginal people. Indicates the potential to reduce health inequalities through nutrition education.